2017
DOI: 10.1108/jima-10-2015-0078
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of support service quality on marketing IS sophistication and bank’s core competencies

Abstract: Purpose The purpose of the study is to examine the moderating effects of support service quality (SSQ) on marketing information services sophistication (MISS) and bank’s core competencies within banking sector. Design/methodology/approach To collect the data, the questionnaire approach and random sampling are chosen. The survey sample consisted of 180 banking branches information technology managers in Sudan’s banking industry. Findings The study evidenced that the effect of SSQ on the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…Amongst the variables, FU is the most critical motivation followed by CA and FC. For instance, it was found that 37.4% of halal fashion buying behaviour is positively influenced by FU (Ezeh and Nkamnebe, 2018; Ali, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the variables, FU is the most critical motivation followed by CA and FC. For instance, it was found that 37.4% of halal fashion buying behaviour is positively influenced by FU (Ezeh and Nkamnebe, 2018; Ali, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…By doing so correctly, Jordanian public universities will be able to achieve the competency profile that will help them maintain a competitive advantage and have an impact on their performance. An individual's capacity to engage successfully with others at work, school, home, and in their communities is referred to as their competency [43]. Competencies can also be information, skills, attitudes, experiences, abilities, or traits.…”
Section: Core Competencymentioning
confidence: 99%
“…Similar to this, an operations core competency is a collection of distinct and recognisable company activities carried out in response to technological advances [14,15]. Any information, skill, attitude, experience, talent, or trait that enables people to interact with us successfully at work, school, home, and in their communities is referred to as competency [16]. According to Amias and Segumpan [17] competence is the quality of being sufficiently or highly qualified and capable of performing well in a certain function.…”
Section: Introductionmentioning
confidence: 99%
“…Core competitiveness is mainly reflected in three aspects: technical knowledge, process, and external relations, where external relations refer to strengthening the relationship with customers while adjusting to the latest policies and technologies to generate a connection with the times [14]. In addition, products and corporate culture also play an important role in core competitiveness [15].…”
Section: Core Competitiveness and Digital Transformation Of Commercia...mentioning
confidence: 99%